2000
DOI: 10.1007/s007050070002
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of columbid circovirus (CoCV), a new circovirus from pigeons

Abstract: The complete nucleotide sequence of columbid circovirus (CoCV) isolated from pigeons is described. CoCV was amplified using a consensus primer PCR approach directed against conserved sequences within the rep genes of vertebrate circoviruses. The genome of CoCV is circular and 2037 nt in size. It displays 55% homology to the genome of psittacine beak and feather disease virus and is more distantly related (< 40% homology) to porcine circovirus type 1 and 2. Two major open reading frames were identified, encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 27 publications
2
102
0
1
Order By: Relevance
“…The major clade (clade 1) based on capsid sequence similarities is considered as the most predominant PiCV in Taiwan and a recent report implicated the potential triggers of this disease in German herds (Mankertz et al, 2000). The other clades are minor groups related to isolates from Germany, England and Italy, indicating the geographicalindependent grouping.…”
Section: Divergences Driven By Positive Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major clade (clade 1) based on capsid sequence similarities is considered as the most predominant PiCV in Taiwan and a recent report implicated the potential triggers of this disease in German herds (Mankertz et al, 2000). The other clades are minor groups related to isolates from Germany, England and Italy, indicating the geographicalindependent grouping.…”
Section: Divergences Driven By Positive Selectionmentioning
confidence: 99%
“…PiCV was first documented in Canada in 1986 (Woods et al, 1994); since then, several outbreaks have been reported in many countries, including Northern Ireland (Smyth & Carroll, 1995;Todd et al, 2001), England (Gough & Drury, 1996), Germany (Mankertz et al, 2000;Raue et al, 2005;Soike, 1997), France (Abadie et al, 2001), Belgium (Duchatel et al, 2006), China (Yu et al, 2009), Hungary (Cságola et al, 2012 and Italy (Coletti et al, 2000;Franciosini et al, 2005). A comprehensive study has demonstrated that PiCV infection is associated with a multifactorial disease known as young pigeon disease syndrome (YPDS) possibly by inducing immunosuppression in infected birds (Raue et al, 2005;Schmidt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Circovirus of the family Circoviridae contains, or is likely to contain, porcine circovirus type 1 and porcine circovirus type 2 (PCV2), psittacine beak and feather disease virus (BFDV) and pigeon or columbid circovirus (PiCV) (Mankertz et al ., 2000;Todd, 2000;Todd et al ., 2001b). Additional candidate members of the genus have also recently been described, namely canary circovirus (Todd et al ., 2001a), goose circovirus (GoCV) (Todd et al ., 2001b) and duck circovirus (Hattermann et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…CoCV is the most frequently detected infectious agent in diseased young pigeons (Soike et al, 2001). The whole genome has been cloned and sequenced (Mankertz et al, 2000), and DNA-based diagnostic procedures have recently been developed Innovation and discovery 585 Kho et al (2000) (Soike et al, 2001). To make the PCR specific for CoCV, oligonucleotides primers were designed based on sequences in the putative cap gene, which exhibits the highest diversity among genes of circoviruses.…”
Section: Discovery Of Circovirusesmentioning
confidence: 99%